Novo-Lenino: criminal activity and rehabilitation - Kudryavtsev, Fedor; Tokareva, Elena (project baikal, 2021)
The results of a crime localization study in Russian cities are presented. A long-term model of urban environment influence on criminal intent is proposed. Social and spatial causes of rising criminal level and later urban reconstruction methods are shown on the example of Pruitt-Igoe (St. Louis) and Bijlmer (Amsterdam) districts. A model for the reconstruction of the Novo-Lenino district in Irkutsk is proposed. Measures have been developed considering the historical dynamics of the region and its unique features.
Keywords: socially disadvantaged areas; crime localization; urban rehabilitation; Novo-Lenino